Ambulatory percutaneous lung biopsy with early discharge and Heimlich valve management of iatrogenic pneumothorax: more for less. Issue 2 (14th July 2015) - Tavare, A N; Creer, D D; Khan, S; Vancheeswaran, R; Hare, S S
Abstract : A prospective study of 489 consecutive outpatient image-guided percutaneous lung biopsies was conducted to determine whether early discharge, incorporating ambulatory Heimlich valve drain, is potentially advantageous to the National Health Service. Patients were discharged at 30 or 60 min, with significant pneumothoraces treated using Heimlich valve. 485 (99.2%) patients were successfully discharged early, 402 at 30 min. 87 (17.8%) patients developed pneumothorax: 52 required Heimlich valve; 5 proceeded to biopsy with Heimlich valve in situ. All drains were removed within 48 h, 38/52 (73.1%) at 24 h. Our results provide evidence for a paradigm shift in UK practice: early discharge lung biopsy, facilitated by ambulatory Heimlich valve, is safe with significant clinical and economic benefits.